2004
DOI: 10.1055/s-2004-835636
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4-Heteroaryl-Substituted Coumarins by Suzuki Cross-Coupling Reactions

Abstract: S y n t h e s i s o f 4 -H e t e r o a r y l -S u b s t i t u t e d C o u m a r i n sAbstract: Palladium-catalyzed coupling of 4-trifluoromethylsulfonyloxycoumarins 1a-d with heteroarylboronic acids 2a-d under the Suzuki reaction conditions affords 4-heteroaryl-substituted coumarins in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…Thus, the Suzuki-Miyaura [36][37][38][39][40][41][42][43][44][45], Stille [37], Negishi [46], Sonogashira [47][48][49], Heck [50,51], and Buchwald-Hartwig [52][53][54] reactions are used to obtain various aryl-, hetaryl-, alkenyl-, alkynyl-, and also N-hetaryl-and amino-containing coumarins in high yield. [Pd]-cat.…”
Section: Functionalization and Modification Of The Coumarin Skeletonmentioning
confidence: 99%
“…Thus, the Suzuki-Miyaura [36][37][38][39][40][41][42][43][44][45], Stille [37], Negishi [46], Sonogashira [47][48][49], Heck [50,51], and Buchwald-Hartwig [52][53][54] reactions are used to obtain various aryl-, hetaryl-, alkenyl-, alkynyl-, and also N-hetaryl-and amino-containing coumarins in high yield. [Pd]-cat.…”
Section: Functionalization and Modification Of The Coumarin Skeletonmentioning
confidence: 99%
“…Suzuki cross-coupling between 4-trifluoromethylsulfonyloxy-di-and trimethylcoumarins and various heteroarylboronic acids yielded 4-heteroaryl-substituted methoxycoumarins in excellent yields (81-96 %) [55]. They are potential cytotoxic and chemopreventing agents against cancer.…”
Section: Synthesis Of 4-heteroaryl-substituted Coumarinsmentioning
confidence: 99%
“…Thus, these compounds ( Fig. 13.57) potentially constitute a new generation of neoflavonoid tubulin binding agents [55]. 4-Amido-and 4-(N-heteroaryl) coumarins constitute an important class of flavonoids, widely occurring in nature and also are components of the structures of more complex natural products; they exhibit a broad range of biological activities.…”
Section: Synthesis Of 4-heteroaryl-substituted Coumarinsmentioning
confidence: 99%
“…In the present work we made an attempt to synthesize furocoumarin derivatives containing an aromatic or heteroaromatic substituent on C 3 by palladium-catalyzed cross-coupling of oreoselone trifluoromethanesulfonate (I) with boronic acid (Suzuki reaction). 4-Halo-and 4-trifluoromethylsulfonyloxycoumarins were successfully involved in Suzuki-Miyaura reaction to synthesize 4-aryl(hetaryl or alkynyl)coumarins [8,9], while analogous reactions with substituted furocoumarins were not reported previously.Cross-coupling of oreoselone trifluoromethanesulfonate (I) with o-tolylboronic acid (II) was used as …”
mentioning
confidence: 98%
“…4-Halo-and 4-trifluoromethylsulfonyloxycoumarins were successfully involved in Suzuki-Miyaura reaction to synthesize 4-aryl(hetaryl or alkynyl)coumarins [8,9], while analogous reactions with substituted furocoumarins were not reported previously. [9,10]. We found that the reaction of oreoselone trifluoromethanesulfonate (I) with o-tolylboronic acid (II) in the presence of Bu 4 N + Br -(10%) requires shorter time (4.5 h) and ensures increased yield of compound III (to 75%).…”
mentioning
confidence: 98%